Car hacking: Navigating the regulatory landscape. Issue 2 (April 2016) - Schellekens, Maurice
Abstract: In the summer of 2015, two American hackers succeeded in hacking into a car and taking over vital functions such as the engine and the brakes. Although this had been done before, the new element of the hack was that it no longer required physical access to the car. The hack took place at a distance via the mobile telephone network. This is a worrying development. It raises the question whether automobile manufacturers are doing enough to counter cyber security threats and, if that is not the case, whether a regulatory intervention is necessary and, if so, how to fashion regulation.